Adaptations to interval training at common intensities and different work:rest ratios
The differences in training adaptations that occurred between two groups when interval training sets of the same speed and intensity were varied across different rest intervals were compared. The selected pace was equivalent to 110% VO2max (400 m speed) and the set was 6 x 100 m. A work to recovery ratio of 1:2 was used in one group and 1:5 in the other. It was found that the short rest group increased in endurance adaptations and lost some sprinting ability. The longer rest group did not change in endurance capability but did increase in sprint capacity. Implication: Between repetitions recovery intervals of less than 30 sec stimulate endurance adaptation. If that is the objective of the training set, it is best to keep the interval less than 15 sec for maximum effects. For anaerobic adaptations to occur, recovery intervals should be in excess of one minute and up to at least twice the duration of the repetition swim. These effects occur independent of the repetition distance or pace.